The Analgesic Efficacy of Prolonged Erector Spinae Fascial Plane Block in Patients with Multiple Rib Fractures - V. H. Sharipova; I. V. Fokin (Общая реаниматология)
Objctive. To evaluate the analgesic efficacy of prolonged erector spinae fascial plane (ESFP) block in patients with multiple rib fractures.Material and methods. The study included 40 patients with multiple rib fractures. Based on anesthesia methods, patients were divided into 2 groups, where systemic analgesics were used for pain management in the control group (N=20), and additional supplementation with prolonged erector spinae fascial plane (ESFP) block in the main group (N=20). The study monitored the severity of pain measured by the numeric rating scale (NRS) at rest and during coughing, forced vital capacity (FVC), and the need for injectable narcotic analgesics.Results. The NRS measures at rest in the main group were statistically significantly superior to the control group results: at stage II — 1.5 points (IQR: 1.0–3.0) vs 3.0 points (IQR: 3.0–4.0); at stage III — 2.0 points (IQR: 1.0–2.0) vs 4.0 points (IQR: 3.0–5.0); at stage IV — 1.5 points (IQR: 0.8–2.2) vs. 4.5 points (IQR: 4.0–5.0); at stage V — 1 point (IQR: 0–2,0) vs. 3.0 points (IQR: 2.8–4.0), respectively (P0.001). Percentages of predicted FVC depending on patient’s gender, age, height and weight in the control group were as follows: at stage II — 38± 8% (95%CI: 34–41); stage III — 44± 8% (95%CI: 40–47); stage IV — 41±10% (95%CI: 36–45) and stage V — 49±10% (95%CI: 45–53). In the main group, the following FVC values were obtained: 49±15% at stage II (95%CI: 42–56), 50±13% at stage III (95%CI: 44–57), 53±13% at stage IV (95%CI: 47–59), and 57±11% at stage V (95%CI: 52–63). Therefore, statistically significant FVC reduction in the control group vs the main group came up to 22%, 14%, 24% and 15% at stages II-V, respectively (P0.05). The amounts of injected narcotic analgesics on day 1 and day 2 after initiation of the study were 5.0 mg (IQR: 5–10) and 5.0 mg (IQR: 0–5.0) in the main group vs 10.0 mg (IQR: 5.0–15.0) and 7.5 mg (IQR: 5.0–10.0) in the control group, respectively (P0.05).Conclusion. The prolonged erector spinae fascial plane block improves the quality of analgesia and FVC values in patients with multiple rib fractures.